HUBUNGAN PENGETAHUAN IBU DAN POLA ASUH TENTANG STATUS GIZI BALITA DENGAN KEJADIAN KEKURANGAN GIZI PADA BALITA DI KELURAHAN BARAN TIMUR KECAMATAN MERAL KABUPATEN KARIMUN - Elyani, Enny; Yunita, Prasida (Universitas Batam, 2019)
Municipal nutritional status is one of the health problems faced by the Indonesian government. One indicator of community nutritional status is the nutritional status of children. The attempt to achieve good nutritional status forspecifically under five year childrenis inseparable from the role of parents, mainly mothers as caregivers andwho are responsible for preparing as well as organizing family members’ meals, comprising for their toddlers. The background of knowledgeof a mother about the food and its nutrition for children is vastlycrucial. The purpose of this study is to determine the correlationof mothers’ knowledge on nutritional status of children and parenting style with the incidence of malnutrition in infants precisely. This study utilized an analytical research design with a cross sectional approach conducted in Kelurahan Baran Timur, Meral, Karimun from March to May 2018. The population taken was all mothers with 3 to 59 months baby and 82 of them were taken as sample through systematic random sampling technique. From the results of the research, 62.2% of mothers have sufficient knowledge on children nutrition, 56.1% of them apply good patenting style, and therefore,76.8% of the toddlers possess good nutritional status. Furthermore, chi-square statistical test verifies that there is a correlation between mothers’ knowledge levels and nutritional status of children with p value= 0.000 <0.05, and there is also correlation between mothers’ parenting style with nutritional status of children indicated by p value= 0.003 <0.05. From the findings, it can be concluded that there is a significant correlation between mothers’ knowledge and their parenting styles with the incidence of malnutrition on under five year children in Kelurahan Baran Timur, Meral, Karimun.Lastly, it is suggestedto the respondents to be more aware on their children nutrition byroutinely attending theposyandu and increasing their knowledge also information by attending parenting seminars, counseling and reading any related books.